KANDUNGAN PROKSIMAT JAMUR LIAR (Volvariella volvacea) PADA TANDAN BUAH KOSONG KELAPA SAWIT (Proximate Content edible wild mushroom Volvariella volvacea On The Empty Fruit Oil Palm Fruit) - Ahmad Mustangin (Universitas Tanjungpura, 2020)
The processing of oil palm fruit in the factory produces waste in the form of empty fruit bunches (EFB). During the decomposition process of EFB into organic materials, it is very easy to grow edible wild mushrooms. Sanggau Regency people call it mushroom pentol. The mushrooms is known as an excellent source of nutrition including macronutrients. This study aims to determine the proximate content of edible wild mushrooms (pentol) that grow on oil palm empty fruit bunches (Elaeis guineensis Jacq). The results showed the water content (wb) was 91.94%; ash content (db) 8.19%; total protein content (db) 47.02%; fat content (db) 17.25%; crude fiber content (db) 5.09% and carbohydrate content (db) 22.45%. So it can be concluded pentol fungus can be a good source of macronutrients.Keywords: empty fruit bunches (EFB), mushroom pentol, proximate Pengolahan buah kelapa sawit di pabrik menghasilkan limbah berupa tandan buah kosong (tankos). Selama proses dekomposisi tankos menjadi bahan organik, dengan sangat mudah tumbuh jamur liar yang edible. Masyarakat Kabupaten Sanggau biasa menyebutnya jamur pentol. Jamur dikenal sebagai sumber nutrisi yang sangat baik termasuk didalamnya makronutrien. Penelitian ini bertujuan untuk mengetahui kandungan proksimat jamur liar edible (pentol) yang tumbuh pada tandan buah kosong kelapa sawit (Elaeis guineensis Jacq). Hasil penelitian menunjukkan kadar air (wb) 91,94%; kadar abu (db) 8,19%; kadar protein total (db) 47.02%; kadar lemak (db) 17.25%; kadar serat kasar (db) 5,09% dan kadar karbohidrat (db) 22.45%. Sehingga dapat disimpulkan jamur pentol dapat dijadikan sumber makronutrien yang baik.Kata Kunci: tankos, jamur pentol, proksimat